2018
DOI: 10.1007/s10787-018-0492-y
|View full text |Cite
|
Sign up to set email alerts
|

The cytotoxic effects of propolis on breast cancer cells involve PI3K/Akt and ERK1/2 pathways, mitochondrial membrane potential, and reactive oxygen species generation

Abstract: Propolis has been extensively used to improve health and prevent inflammatory diseases. Different types of Cuban propolis (red, brown and yellow) have been documented. The purpose of this research was to investigate the cytotoxic effects of Cuban red propolis (CP) on MDA MB-231 cell line, since breast cancer is considered one of the most common causes of mortality among women. Antiproliferative and cytotoxic activity of CP against MDA MB-231 cells were determined by the 3-[4,5-dimethylth-iazol-2-yl]-2,5-diphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 31 publications
0
17
0
1
Order By: Relevance
“…The diversified results obtained may be due to more than 300 constituents of propolis samples (including benzoic acid, cinnamic acid, flavonoids) [ 62 ], which probably causes interactions between compounds of a synergistic, additive, or antagonistic nature. Inhibition of cancer cell migration by propolis extracts and individual components has been confirmed, among others, for glioblastoma, prostate, colorectal, lung, bladder, as well as breast cancer cells (MCF-7) [ 63 , 64 , 65 , 66 , 67 , 68 ].…”
Section: Resultsmentioning
confidence: 89%
“…The diversified results obtained may be due to more than 300 constituents of propolis samples (including benzoic acid, cinnamic acid, flavonoids) [ 62 ], which probably causes interactions between compounds of a synergistic, additive, or antagonistic nature. Inhibition of cancer cell migration by propolis extracts and individual components has been confirmed, among others, for glioblastoma, prostate, colorectal, lung, bladder, as well as breast cancer cells (MCF-7) [ 63 , 64 , 65 , 66 , 67 , 68 ].…”
Section: Resultsmentioning
confidence: 89%
“…Extracts induce apoptosis by activating TP53, CASP3, BAX, p21 signaling and downregulating BCL2, BCL-XL, and PUMA. But in a similar study, researchers found that Brazilian propolis did not affect BCL-2, BCL-XL, NOXA, and PUMA expression [ 108 , 109 ].…”
Section: Mechanisms Of Anticancer Activity Of Propolis and Its Compoundsmentioning
confidence: 99%
“…Ethanolic extract of propolis and its active components (CAPE) are reported to exhibit antioxidant, cytotoxic, pro-apoptotic, autophagic, and anti-inflammatory activities in lipopolysaccharide stimulated MDA-MB-231 breast cancer cells by suppressing the TLR-4 signaling pathway [68][69][70]. Frión-Herrera and colleagues [71] demonstrated that treatment of breast cancer cells with propolis and its active ingredient (cardanol) triggered apoptosis (cytotoxicity) by modulation of PI3K/Akt, p38 MAPK, and ERK1/2 signaling pathways as well as by enhancing ROS generation and subsequent loss of mitochondrial potential. Propolis displays strong anti-proliferative and induces cell cycle arrest (G0/G1 and G2/M phase) by upregulating p21 and p27 expression [72].…”
Section: Chemopreventive On Breast Cancer and Underlying Mechanismsmentioning
confidence: 99%